Increased thrombin activatable fibrinolysis inhibitor activity is associated with hypofibrinolysis in dogs with sepsis - Sotos, Katherine E.; Goggs, Robert; Stablein, Alyssa P.; Brooks, Marjory B. (Frontiers in Veterinary Science, 2023)
Introduction Disorders of coagulation are well-recognized in dogs with sepsis, but data regarding fibrinolysis disorders are limited. We aimed to characterize fibrinolysis in dogs with sepsis compared to healthy controls. We hypothesized that dogs with sepsis would be hypofibrinolytic, and that hypofibrinolysis would be associated with non-survival. Methods This was a prospective observational cohort study. We enrolled 20 client-owned dogs with sepsis admitted to the Cornell University Hospital for Animals and 20 healthy pet dogs. Coagulation and fibrinolytic pathway proteins including antiplasmin activity (AP), antithrombin activity (AT), thrombin activatable fibrinolysis inhibitor activity (TAFI), D-dimer concentration, fibrinogen concentration, and plasminogen activity were measured and compared between groups. Overall coagulation potential, overall fibrinolysis potential, and overall hemostatic potential were calculated from the curve of fibrin clot formation and lysis over time. Results Compared to healthy controls, dogs with sepsis had lower AT (P = 0.009), higher AP (P = 0.002), higher TAFI (P = 0.0385), and higher concentrations of fibrinogen (P < 0.0001) and D-dimer (P = 0.0001). Dogs with sepsis also had greater overall coagulation potential (P = 0.003), overall hemostatic potential (P = 0.0015), and lower overall fibrinolysis potential (P = 0.0004). The extent of fibrinolysis was significantly negatively correlated with TAFI. No significant differences were observed between survivors and non-survivors. Discussion Dogs with sepsis were hypercoagulable and hypofibrinolytic compared to healthy dogs, suggesting potential utility of thromboprophylaxis in this patient population. The association between high TAFI and low overall fibrinolysis potential might provide a potential mechanism for this hypofibrinolysis.